The Erotics of Consolation
VIII, 241 p.
Keywords: This collection of essays explores consolation and mourning in the varied, sometimes provocative, readings of Boethius and of Stoic consolation by French, English, Italian and German authors, including Dante, Petrarch, Boccaccio, Machaut, Chaucer, Wyatt and Queen Elizabeth I.